(untitled) (Journal of the College of Education for Women, 2019)
This research attempts to investigate narrative structure in oral narrative particularly in Oprah’s Show from a sociolinguistic viewpoint. Narrative is said to be universal in the sense that it is found in all times and places. There is no society or culture without narrative. Oral narrative is organized in a specific order. The research aims at studying and analyzing this order. In addition to that, it highlights the importance of narrative in conveying some moral messages to people who are listening to the story. The study is divided into two parts; theoretical and practical. The theoretical part draws on presenting a survey of literature which includes definitions and explanations of some related terms. The practical part is concerned with the analysis of the selected data. One episode from Oprah’s Show is chosen for the analysis. The analysis of the data is carried out on the basis of Labov’s (1972) model. The results show that (1) oral narrative depends mostly on real stories and participants.(2) Oral narrative follows a certain order and contains elements that are not found in written narrative such as, abstract and evaluation.